2018
DOI: 10.18805/a-398
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence landrace of langsat (Lansium parasiticum) from Siberut Island based on ITS and MatK markers

Abstract: Langsat is a specific potential of tropical fruit, especially in the Southeast Asia region. The center of distribution this species in Indonesia is Sumatra region, including the Siberut Island. There are some local germplasms (landraces) of langsat from Siberut Island namely Seccet, Siamung, Telu toru gokgok, Elakmata, and Langsat padang. Analysis of genetic diversity and genetic divergence is very important for sustainable utilizing of this tropical fruit. Based on analyzed of fourteen accessions of langsat u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…macroura. The results of previous studies also revealed the morphological differences between cultivated variety from the different geographical regions (Moawed, 2015;Strbanovic et al, 2015) and between the wild infra-specific taxa (Tripathy et al, 2016;Huda et al, 2019) were detected.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…macroura. The results of previous studies also revealed the morphological differences between cultivated variety from the different geographical regions (Moawed, 2015;Strbanovic et al, 2015) and between the wild infra-specific taxa (Tripathy et al, 2016;Huda et al, 2019) were detected.…”
Section: Resultsmentioning
confidence: 76%
“…Furthermore, molecular evidence is a significant character to support the stable identification of a taxon and classification of the taxonomic group. The haplotype is a set of DNA that can be used to identify differentiation between accessions (Huda et al, 2019) or infraspecific and species. In this study, the haplotype analysis was carried out on eleven sequences that consisting of seven sequences obtained from this study and four other sequences of DNA Clarification of Sumatran Mulberry (Morus macroura var.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular characterization and identification play a vital role in distinguishing plants at the level of individuals, populations, races, and plant species (Huda et al, 2019;Nuratika and Aseny, 2020). However, various molecular techniques applied to distinguish between plant groups were generally DNA sequencing or RAPD and SRAP techniques.…”
Section: Discussionmentioning
confidence: 99%
“…All the five variants of langsat were locally called Lansat Padang, Attelu turugougou, Siamung, Elak mata, and Setcet. Huda et al state that there are five local germplasms of Langsat from Siberut and based on the phylogenetic trees showed that the accessions of langsat from Siberut Island were separated from accessions of Sumatran mainland [10]. While for durian's germplasm, Mentawai durian (Durio lowianus), locally called Toktuk, was different from durians found on the mainland Sumatra (Durio zibethinus).…”
Section: Plant Species and Their Uses In Various Land Types In The Traditional Plantation In Mentawaimentioning
confidence: 99%